Literature Review: Pendidikan kesehatan melalui diskusi kelompok dan curah pendapat terhadap pengetahuan dan sikap Pasangan Usia Subur (PUS) Akseptor KB AKDR - Nazirah Nazirah; Putri Santy; Nurlaili Ramli; Eva Purwita (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: There has been a decrease in the number of IUD family planning acceptors in the last three years, from 3.69% in 2016 to 3% in 2017 and 2018. One factor in the low use of IUD contraceptives is public perception. The way to change people's negative perceptions about the IUD is to provide health education.Objectives: To review several journals about effect of health education about iud (intrauterine) device uses group discussion and brainstorming on the level of knowledge and attitudes fertile age couples.Methods: The study is a literature review method based on the articles searched on Google Scholar and PubMed. The keywords used to find articles were using the keywords "Health Education, IUD, Group Discussion, Brainstorming, Knowledge, and Attitudes". The data obtained were compiled, analyzed and concluded by looking for similarities, inequalities providing views, comparing and summarizing.Results: Literature review shows that there is an effect of health education with the method of group discussion and brainstorming on a person's knowledge and attitudes.Conclusion: Health education using the group discussion method has more influence on increasing knowledge and attitudes. It is hoped of the health institutions can improve health services by providing information through health education to the public about the benefits of intrauterine contraceptives (IUDs).